2011
DOI: 10.1179/1743284711y.0000000070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multicomponent modifier on microstructure and mechanical properties of high Ni–Cr–Mo cast iron

Abstract: The microstructure and mechanical properties of high Ni–Cr–Mo indefinite chilled cast iron with the addition of a newly developed multicomponent modifier consisting of mixed rare earths, Si–Ca alloy and Bi–Sb alloy have been investigated through optical microscopy, X-ray diffraction and scanning electron microscopy, along with hardness, impact toughness and wear resistance measurements. After the addition of the modifier, the grain sizes of the primary austenite and eutectic carbides are found to be greatly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In this case, it is verified that this effect also reaches the region of the shell in contact with the core. In previous studies by the authors, it was similarly found that if the ladle is not inoculated with FeSi-La, then there is an improvement in the impact toughness inside the working layer [29,30,32]. In the present study, we have verified that this effect is maintained in the region of the shell-core bond.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this case, it is verified that this effect also reaches the region of the shell in contact with the core. In previous studies by the authors, it was similarly found that if the ladle is not inoculated with FeSi-La, then there is an improvement in the impact toughness inside the working layer [29,30,32]. In the present study, we have verified that this effect is maintained in the region of the shell-core bond.…”
Section: Resultssupporting
confidence: 86%
“…Setting both factors at their respective +1 (0.6 kg/T SiCaMn) and −1 (without FeSi-La) levels leads to an increase in said toughness. In a previous study by the authors, it was found that inoculation with SiCaMn promoted discontinuity of the carbide network [32], which increased the toughness of the shell [29]. In this case, it is verified that this effect also reaches the region of the shell in contact with the core.…”
Section: Resultsmentioning
confidence: 71%
“…The composition of FeSi alloys includes elements such as Ca, Al, and Ba, which, due to their high affinity with O, precipitate forming small oxide particles that can act as agents for the nucleation of graphite [19]. The use of inoculants with high percentages of Ca may promote a decrease in the grain size of the primary austenite and discontinuity of the carbide network [20]. La could increase the number of counts of graphite [21] and promote a finer structure of the carbide network [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mg acts as a nucleator of graphite [20]. Inoculation with SiCa promotes a decrease in the grain size of the primary austenite and discontinuity of the carbide network [21], which could increase the toughness of the material. The presence of Lanthanum improves the mechanical properties of white cast irons [22].…”
Section: Introductionmentioning
confidence: 99%